Mitigasi Sejak Dini Hipertensi pada Penyintas Bencana Tanah Bergerak Desa Mendala Kabupaten Brebes - Zuhri, Fuad Minan; Indarwati, Uli Mas’uliyah; Sulistiyowati, Retno; Mujahid, Ikhsan; Fajri, Ahmad (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to enhance knowledge and awareness of disaster-related hypertension and its associated health risks, while simultaneously facilitating early detection of elevated blood pressure among survivors residing in Mendala Village Brebes Regency. The activity involved health counseling, health checks, and free medication for 140 survivors. This activity was carried out through three stages: planning, implementation, and evaluation. The results of blood pressure checks were 50 people who experienced hypertension 1, 2 and systolic, with risk factors mostly middle-aged, elderly and old age as much as 75.6%, and 35.2% were active smokers from men. The evaluation showed a high level of participation and enthusiasm in participating in this activity, where survivors received education related to disaster hypertension, screening, health consultation and free medicine.